2020
DOI: 10.1186/s13102-020-00181-0
|View full text |Cite
|
Sign up to set email alerts
|

Periodized resistance training for persistent non-specific low back pain: a mixed methods feasibility study

Abstract: Background: We investigated the feasibility of a 16-week supervised heavy resistance training program with weekly undulating periodization for individuals with persistent non-specific low-back pain (LBP). Methods: Twenty-five adults with persistent non-specific LBP participated in this mixed methods feasibility study. Participants trained a whole-body program consisting of squat, bench press, deadlift and pendlay row two times per week for 16 weeks. We assessed pain intensity, pain-related disability, pain sel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…However, a greater number of program sessions and a greater total volume of training minutes per week did not translate into greater reduction in pain. Interestingly, interventions ≤8 weeks induced greater pain reduction than those of >8 weeks (ES = −6.12 vs. ES = −0.94, respectively), contrary to previous research (24,45,51,86) that demonstrated a decrease in pain when higher volumes of training (i.e., higher weekly frequency and appropriate training periodization) were performed.…”
Section: Discussioncontrasting
confidence: 93%
“…However, a greater number of program sessions and a greater total volume of training minutes per week did not translate into greater reduction in pain. Interestingly, interventions ≤8 weeks induced greater pain reduction than those of >8 weeks (ES = −6.12 vs. ES = −0.94, respectively), contrary to previous research (24,45,51,86) that demonstrated a decrease in pain when higher volumes of training (i.e., higher weekly frequency and appropriate training periodization) were performed.…”
Section: Discussioncontrasting
confidence: 93%
“…Meadows row also can use greater loads because of a widened stance, support through the contralateral upper extremity, and favorable mechanical advantage. Compared with free-weight variations such as the Pendlay row (70) and dumbbell wide row (27), Meadows row guides glenohumeral horizontal abduction, a movement more difficult to control than extension, particularly for athletes with shoulder instability (75).…”
Section: Exercise Variationsmentioning
confidence: 99%
“…The row is a multi-joint exercise that involves pulling resistance toward the body via actions of the shoulder complex and elbow (27,57). The usefulness of rowing exercises is wellestablished for training muscles of the back (14,17,50,56), assessing pulling strength and power (19,51), differentiating between sport skill level (e.g., pace bowling in cricket) (39), potentiating pushing power in contrast training (2), and rehabilitating injuries (13,54,55,70).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, multiple factors have been associated with the occurrence of NSLBP [9,10], including deconditioning the lumbar musculature [11,12], reduced trunk muscle mass [13], imbalance, and decreased trunk strength [14,15]. Thus, trunk strengthening has been proposed for manage LBP patients [16][17][18]. Furthermore, different trunk training methods have been investigated, such as motor control exercises [19], core stabilization [20,21], and strengthening exercises using an isokinetic dynamometer [22].…”
Section: Introductionmentioning
confidence: 99%